Challenges for private sector job matching in rural Egypt: Results from a survey of Forsa employers - Shokry, Nada; Yassa, Basma; Kurdi, Sikandra (International Food Policy Research Institute, 2024)
Increasing formal employment for youth and women is a key goal of the Forsa pilot graduation intervention and Egyptian government policy in general. As detailed in Forsa evaluation reports, matching Takaful beneficiaries with jobs in the private sector is a major challenge on the household and on the beneficiary level. In this policy note, however, we examine the challenges from the perspective of potential employers. We review literature of the market failures that may contribute to difficulties with job matching in rural Egypt and present results from a small telephone survey of Forsa employers.